Hubungan antara Set Kesempatan Investasi dengan Kebijakan Pendanaan dan Dividen, serta Leverage Financial - Shanti, .; Wulaningrum, Ratna (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2005)
The objectives of this study are to investigate the association between the investment opportunity set (IOS) values as firm growth proxy and realized firm growth, corporate financing, dividend policies, and leverage financial. Five proxies IOS are used as firm growth indicator such as